2000
DOI: 10.1088/0953-8984/12/7/303
|View full text |Cite
|
Sign up to set email alerts
|

Theory of self-diffusion in alkali metals: I. Results for monovacancies in Li, Na, and K

Abstract: The phonon dispersion curves for perfect crystals of bcc Li, Na, and K are calculated by the ab initio force-constant method in a supercell approach. It is shown that the coupling constants of Li decay much more slowly in space than those for Na and K, so for Li the phonon spectrum could not be reliably determined with the supercell sizes used in the calculations. From the phonon spectra of the perfect supercell and the supercell with a monovacancy the vacancy formation entropy is calculated for Na (1.36 k B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 64 publications
7
30
0
Order By: Relevance
“…Examples are calculations on Li, 1, 2) Na 2,3) and, in particular, on Al, the subject of the present paper. Based on the density functional theory (DFT), 4) the majority of the computations make use of the local density approximation (LDA) of Kohn and Sham,5) whose reliability in this context can at present not be judged by theoretical arguments alone.…”
Section: Introduction and General Backgroundmentioning
confidence: 98%
See 1 more Smart Citation
“…Examples are calculations on Li, 1, 2) Na 2,3) and, in particular, on Al, the subject of the present paper. Based on the density functional theory (DFT), 4) the majority of the computations make use of the local density approximation (LDA) of Kohn and Sham,5) whose reliability in this context can at present not be judged by theoretical arguments alone.…”
Section: Introduction and General Backgroundmentioning
confidence: 98%
“…13) Therefore the tracer self-diffusivity, D T (T ), may be obtained accurately even at temperatures T that are so low that a substantial fraction of the thermalequilibrium vacancies is associated with impurities. (2) In contrast to bcc metals such as Li, Na, etc., fcc metals do not undergo low-temperature phase transformations that affect the self-diffusivity by fluctuation enhancement. 14,15) Whereas in quite a few fcc metals H SD 1V is known from experiment with an accuracy of about 1%, it is much more difficult to obtain the quantities on the left-hand side of eq.…”
Section: Introduction and General Backgroundmentioning
confidence: 99%
“…35,36 Experimental and computational studies have shown that the self-diffusion mechanism in bulk Li and Na metal is dominated by monovacancy transport. 37 Under thermal equilibrium, the overall activation energy for self-diffusion = is , + , given as the sum of the vacancy formation energy, , and the activation energy, . DFT calculations have indicated that the activation energies of monovacancies in Li ( 0.053 eV) = and Na ( 0.053 eV) are considerably smaller than the = formation energies ( =0.506 eV and =0.334 eV).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the phonon dispersion of alkali metals has been calculated by many model methods, such as pair potentials [2][3][4], the general tensor force model [5], the embedded atom method (EAM) [6], analytic EAM (AEAM) [7,8], ab initio [9][10][11][12], and pseudopotential theory [13]. For instance, the phonon dispersion of alkali metals has been calculated by many model methods, such as pair potentials [2][3][4], the general tensor force model [5], the embedded atom method (EAM) [6], analytic EAM (AEAM) [7,8], ab initio [9][10][11][12], and pseudopotential theory [13].…”
Section: Introductionmentioning
confidence: 99%